2018
DOI: 10.31661/jbpe.v0i0.827
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetry and Radioenhancement Comparison of Gold Nanoparticles in Kilovoltage and Megavoltage Radiotherapy using MAGAT Polymer Gel Dosimeter

Abstract: Background: Numerous unique characteristics of the nanosized gold, including high atomic number, low toxicity, and high biocompatibility make it one of the most appropriate nanostructures to boost radiotherapy efficacy. Many in-vivo and in-vitro investigations have indicated that gold nanoparticles (AuNPs) can significantly increase tumor injuries in low kilovoltage radiotherapy. While deep-lying tumors require much higher energy levels with greater penetration power, and investigations carried out in megavolt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The importance of this increment is that, when the polymer gel is irradiated, more energy will be deposited due to higher generations of photoelectrons resulted from the presence of ZnO NPs in the polymer gel which may lead to an increase in gel sensitivity. The sensitivity enhancement in the polymer gel dosimeter is essential to reduce a certain amount of absorbed dose to the patient while also being able to reduce random errors in radiotherapy treatment (11) . These results are in good agreement with those reported by Mustaqim et al, (26) and Banaee et al, (27) which showed that when the ZnO was added into the polymer gel formulation, the polymer gel's sensitivity increased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of this increment is that, when the polymer gel is irradiated, more energy will be deposited due to higher generations of photoelectrons resulted from the presence of ZnO NPs in the polymer gel which may lead to an increase in gel sensitivity. The sensitivity enhancement in the polymer gel dosimeter is essential to reduce a certain amount of absorbed dose to the patient while also being able to reduce random errors in radiotherapy treatment (11) . These results are in good agreement with those reported by Mustaqim et al, (26) and Banaee et al, (27) which showed that when the ZnO was added into the polymer gel formulation, the polymer gel's sensitivity increased.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of published studies on the significance and influence of nanoparticles on dose amplification in polymer gel dosimeter application (7)(8)(9)(10) . The fact that photoelectric chance increases when metal is presence inside a biological target leads to an increased dose absorption has driven the nanoparticle application in radiotherapy (radionanotherapy) (11) . This process takes advantage of the high mass-energy absorption coefficient (μen/ρ) of these materials relative to tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, addition of high atomic elements (such as bismuth, gadolinium, silver or gold nanoparticles, etc.) has been investigated for increasing photon sensitivity [ 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ].…”
Section: Polyacrylamide Gelsmentioning
confidence: 99%
“…Various studies have analyzed the MRI response of polymer gels for possible application in radiotherapy dose mapping ([ 58 , 63 ] and references therein). In particular, polymer gels have been investigated for dosimetry in conformal therapy, IMRT, IMAT, IGRT, VMAT and tomotherapy [ 55 , 70 , 83 , 88 , 102 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 ], small photon fields [ 136 , 137 , 138 ], stereotactic radiosurgery [ 55 , 139 , 140 , 141 , 142 ], 60-cobalt source [ 143 , 144 ], brachytherapy [ 55 , 85 , 92 , 145 , ...…”
Section: Polyacrylamide Gelsmentioning
confidence: 99%